THE HIGHLY DEVELOPED INFORMATION AND EDUCATION ENVIRONMENT AS A PRECONDITION OF EDUCATIONAL SYSTEM REORGANIZATION - Y. K. Khenner (Russian State Vocational Pedagogical University, 2015)
The paper regards the development of the information and education environment of Russian universities as an important condition for successful reorganization of higher education. Taking as an example one of theUSuniversities, the author demonstrates the capacity of information education environment and its impact on the multilevel educational process. The comparative analysis of the existing information education environments of Russian an American universities reveals that such effective improvements as increasing number of students working on the individual curricula,__ implementation of the learning outcome monitoring, inclusive education, etc require immediate and substantial development of the information education environment of Russian universities. Both the development level and informational content of the environment in question remain unsatisfactory due to the financial, economic and staff related reasons. Consequently, the higher school reorganization is lagging behind retarded by the lack of synchronization between the attempts to improve the education quality and competitiveness on the one hand, and insufficient level of the information education environment characteristic of Russian universities on the other hand.